2016
DOI: 10.2337/dc16-0194
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Microvascular Disease Outcomes in Patients With Type 2 Diabetes After Bariatric Surgery: Evidence for the Legacy Effect of Surgery

Abstract: OBJECTIVETo identify and quantify any legacy effect of bariatric surgery on risk of incident microvascular disease in patients with type 2 diabetes.RESEARCH DESIGN AND METHODSWe conducted a retrospective observational cohort study (n = 4,683; 40% racial/ethnic minority) of patients with type 2 diabetes who underwent bariatric surgery from 2001 through 2011. The primary outcome measure was incident microvascular disease defined as a composite indicator of the first occurrence of retinopathy, neuropathy, and/or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
46
0
7

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 93 publications
(59 citation statements)
references
References 26 publications
6
46
0
7
Order By: Relevance
“…This aligns the theory of ‘metabolic memory’, introduced into a RYGB setting by Coleman et al . suggesting that even though a RYGB‐operated individual with Type 2 diabetes relapses into hyperglycaemia after a period of remission, the time spent in remission is a positive predictor for fewer microvascular complications. Finally, by using a less strict definition of diabetes remission there is a chance that our two subgroups of RYGB‐operated individuals are so similar that it has masked a true difference.…”
Section: Discussionmentioning
confidence: 99%
“…This aligns the theory of ‘metabolic memory’, introduced into a RYGB setting by Coleman et al . suggesting that even though a RYGB‐operated individual with Type 2 diabetes relapses into hyperglycaemia after a period of remission, the time spent in remission is a positive predictor for fewer microvascular complications. Finally, by using a less strict definition of diabetes remission there is a chance that our two subgroups of RYGB‐operated individuals are so similar that it has masked a true difference.…”
Section: Discussionmentioning
confidence: 99%
“…Simulation models have suggested that delaying the onset of diabetes delays the onset of complications and comorbidities and reduces their cumulative incidence, partly because of competing mortality (24,25). A recent study indicates that even temporary partial remission reduces the risk of incident microvascular disease (26). However, further research is needed to measure the magnitude of the effect on other outcomes such as complications, comorbidities, and survival.…”
Section: Discussionmentioning
confidence: 99%
“…Further, those with type 2 diabetes who underwent BS experienced the benefit of reduced microvascular outcomes, although long-term data on large number of patients are limited (37). Long-term outcome studies of up to 6.9 years have shown BS to be associated not only with improved glucose control but also with reduced rates of hypertension, hyperlipidemia and cardiovascular mortality (38,39).…”
Section: Bariatric Surgery and Diabetes Remissionmentioning
confidence: 99%